Persistent dyselectrolytemia in a neonate induced by liposomal amphotericin B. A case report - Adrian Puertas Sanjuan; Carlos Javier Parramón-Teixidó; Susana Hernandez-Perez; Marie Antoinette Frick; Maria Jose Cabañas Poy (Frontiers Media S.A., 2023)
BackgroundNephrotoxicity is the most frequent serious adverse effect associated with amphotericin B deoxycholate treatment, for this reason, in recent years it has been relegated from routine clinical practice and replaced by the new liposomal formulations that have less nephrotoxicity. Nevertheless, dyselectrolytemia are a frequent adverse effect of the use of liposomal amphotericin B that usually are resolved with the withdrawal of the drug.Case presentationWe present a preterm neonate of 25 weeks gestation, with preserved renal function and most electrolytes within normal limits for gestational age except for mild hyponatremia in the first month of life. Due to an infection of the central nervous system and growth of Candida albicans, he required treatment with endovenous liposomal amphotericin B as well as intrathecal amphotericin B deoxycholate showing severe hydroelectrolyte disturbances and clinical worsening compatible with possible tubulopathy showing hypokalemia and severe hyponatremia a few days after starting treatment that persisted over time even after withdrawal of both drugs. Subsequently to the main alterations described, hypomagnesemia, hypophosphatemia, glycosuria and tubular proteinuria were also observed. Calcium levels remained stable after amphotericin B administration and did not require supplementation. In preterm or low birth weight newborns who present unjustified, severe and difficult to correct hydroelectrolyte disturbances despite the usual treatment, a possible tubulopathy should be considered, whether hereditary, primary or secondary to toxins or drugs.What Is New and ConclusionWe present the first case reported in a neonate in whom dyselectrolithemia has been maintained over time after withdrawal of liposomal amphotericin B.